Parental supervision and its relation with personality type A.B among high Schools students (Journal of the College of Education for Women, 2019)
Parents who give their sons arole in making parental decisions and admiring their views are the ones who build confidence and the feeling of competence within themselves and then their edgiest- rent with themselves becones better .The (A.B) person-ality type is the core base of most psychological and educational studies because it is one of the most important subjects Concerning with the study of growth aspects whether they are physical, mental or Social. The present Study ains to measure the level of parental treatment among high School students, measure the level of (A) Personality type concept among them, recognize Statistically Significant differences in the level of parentaltreatment according gender variable and recognize the Correlation between parental treatment and the Concept of (A.B) Personality type among high School Students, The Sample consists of (140) male and female Students (70) males and (70) females whom chosen randomly,noting that the 1stsample ofscale builaingdifferes from the basicone. The researcher reaches to a number of results:1-The sample-according to the comparison between arithmetic mean and hypothetical one-subset to parental supervision at (0,05) level.2-The sample-according to the Comparison between arithmetic mean and hypothetical one-has A.B personality type at (0,05) significant level.3-The sample results, according to the difference between arithmetical mean and hypothetical mean, show that the secondary school students have type A personality at (0.05).4-There are significant differences between males and females in parental monitoring at level of (0.05).5-There are significant differences between in personality type (B) according to the gender factor (male and females) at level of (0.05) in favor of females.6-There are no significant differences between in personality type (A) according to the gender factor (male and females) at level of (0.05).7-There is a correlation between parental monitoring and personality type (A and B) which was (0.36) for parental monitoring with personality type (A), and (0,22) for parental monitoring with personality type (B) at a significant level of (0.05).